Nuclear energy now : - Herbst, Alan M. (John Wiley & Sons, 2007)
The dramatic increases in oil and natural gas prices, the finite supply of fossil fuels, and concerns over emissions and global warming are forcing us to consider alternatives. In this measured and knowledgeable book, energy experts Alan Herbst and George Hopley argue that the time has come for the U.S.